Correction: Self-Assembly of Binderless MXene Aerogel for Multiple-Scenario and Responsive Phase Change Composites with Ultrahigh Thermal Energy Storage Density and Exceptional Electromagnetic Interference Shielding - Zhu, Chuanbiao; Hao, Yurong; Wu, Hao; Chen, Mengni; Quan, Bingqing; Liu, Shuang; Hu, Xinpeng; Liu, Shilong; Ji, Qinghong; Lu, Xiang; Qu, Jinping (Nano-Micro Letters, 2025)
The severe dependence of traditional phase change materials (PCMs) on the temperature-response and lattice deficiencies in versatility cannot satisfy demand for using such materials in complex application scenarios. Here, we introduced metal ions to induce the self-assembly of MXene nanosheets and achieve their ordered arrangement by combining suction filtration and rapid freezing. Subsequently, a series of MXene/ K+/paraffin wax (PW) phase change composites (PCCs) were obtained via vacuum impregnation in molten PW. The prepared MXene-based PCCs showed versatile applications from macroscale technologies, successfully transforming solar, electric, and magnetic energy into thermal energy stored as latent heat in the PCCs. Moreover, due to the absence of binder in the MXene-based aerogel, MK3@PW exhibits a prime solar–thermal conversion efficiency (98.4%). Notably, MK3@PW can further convert the collected heat energy into electric energy through thermoelectric equipment and realize favorable solar–thermal–electric conversion (producing 206 mV of voltage with light radiation intensity of 200 mw cm−2). An excellent Joule heat performance (reaching 105 °C with an input voltage of 2.5 V) and responsive magnetic–thermal conversion behavior (a charging time of 11.8 s can achieve a thermal insulation effect of 285 s) for contactless thermotherapy were also demonstrated by the MK3@PW. Specifically, as a result of the ordered arrangement of MXene nanosheet self-assembly induced by potassium ions, MK3@PW PCC exhibits a higher electromagnetic shielding efficiency value (57.7 dB) than pure MXene aerogel/PW PCC (29.8 dB) with the same MXene mass. This work presents an opportunity for the multi-scene response and practical application of PCMs that satisfy demand of next-generation multifunctional PCCs. Highlights: 1 This work proposes a tactic for improving the efficiency of thermal energy conversion and expanding the application scenarios of phase change materials by constructing non-binder and oriented MXene-K+ aerogel. 2 The prepared phase change composites (PCCs) can rapidly transform solar, electric, magnetic energy into latent heat for keeping warm, power generation, and thermal physiotherapy. 3 Owing to the suggested tactic, the prepared PCCs achieves ultrahigh energy storage density and realize 99.9998% electromagnetic wave energy attenuation.